Pengaruh Gaya Kepemimpinan Transaksional dan Transformasional Terhadap Kinerja Karyawan Bank BRI Purworejo - Burhanudin Burhanudin; Agus Kurniawan (Coopetition : Jurnal Ilmiah Manajemen, 2020)
The objectives of this study are: (1) To determine the effect of transactional leadership style on the performance of BRI Purworejo Branch employees; and (2) To determine the effect of transformational leadership style on the performance of BRI Purworejo Branch employees. The sample in this study were all employees of BRI BRI Purworejo Branch, totaling 80 people. Therefore the sampling method in this study uses the census method. The results showed that the transactional leadership style had a positive and significant effect on employee performance. Transformational leadership style has a positive and significant effect on employee performance.